Seismic performance assessment of structures in Malatya Province after 6 February 2023 Turkey earthquake sequences - Ozmen, Alper; Ince, Ozan; Tas, Omer Faruk; Atar, Muhammed; Ozbulut, Osman E.; Sayin, Erkut (Springer, 2025)
On February 6, 2023, at 04:17 and 13:24 local time, two major earthquakes struck Pazarc & imath;k and Elbistan districts of Kahramanmara & scedil;, Turkey. The first earthquake had a moment magnitude of the Mw = 7.7 at a depth of 8.6 km, while the second earthquake had a magnitude of the Mw = 7.6 at a depth of 7 km. The earthquakes impacted eleven cities in Turkey, with a combined population of approximately 15 million people. Reports indicate over 53,000 casualties in Turkey, with more than 230,000 buildings collapsing or suffering severe damage. This paper presents the findings of a post-earthquake reconnaissance field mission by describing the damage sustained in Malatya province. To this end, a summary of the strong ground motion data measured during two earthquakes at different stations is provided first. Subsequently, a more detailed evaluation of the ground motion parameters is presented for the data collected from seismic stations located in Malatya. An assessment of the damage observed in various structures, such as reinforced concrete, precast concrete, masonry, and steel structures, within the Malatya province is presented then. Finding of this study indicates that deficiencies in material quality (poor concrete quality, corrosion in steel and cold joint), improper manufacturing process and design mistakes (weak column-strong beam, short column, adjacent buildings, soft and weak story) are the major causes of the damage observed in Malatya.
Keywords: 2023 Pazarcik-Elbistan (Kahramanmara & scedil;) earthquakes; Reinforced concrete structures; Masonry structures; Steel structures; Structural failures